อัตราการตรวจพบของโรคตับอักเสบเรื้อรังที่ไม่ทราบสาเหตุในกลุ่มโรคตับอักเสบเรื้อรังที่ไม่พบสาเหตุจากไวรัสบี,ไวรัสซี และอัลกอฮอล์ ในโรงพยาบาลจุฬาลงกรณ์ - สมบัติ ตรีประเสริฐสุข (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
Objectives: To determine the detection rate of cryptogenic chronic hepatitis among non alcoholic and non viral hepatitis B, non viral hepatitis C chronic hepatitis patients and to assess the clinical and laboratory findings prospectively. Methods: Thirty-six patitents with negative for markers of viral hepatitis B and viral hepatitis C and who gave no history of alcohol consumption or consumption less than 20 grams of ethanol per day were recruited with consented for liver biopsy and blood tests for identify the etiology of chronic hepatitis. Results: Eight of 36 patients (22.2%) were classified as cryptogenic chronic hepatitis. Most patients (72.2%) exhibited fatty metamorphosis of the liver which included steatosis as well as steatohepatitis. There were statistically significant differences between the fatty metamorphosis group and the cryptogenic chronic hepatitis group with regarding to fasting blood sugar, serum alkaline phosphatase, serum ferritin and histologically necroinflammatory grading score (p<0.05). Between the steatosis and the steatohepatitis, body mass index (BMI) was the only factor showing statistically significant difference (p = 0.02). Conclusion: Steatohepatitis and steatosis are the most common findings of non alcoholic and non viral hepatitis B, non viral hepatitis C chronic hepatitis, especially in the diabetic, the obese patients and those with high serum ferritin level. Cryptogenic chronic hepatitis is not uncommon in our study in Thai patients Objectives: To determine the detection rate of cryptogenic chronic hepatitis among non alcoholic and non viral hepatitis B, non viral hepatitis C chronic hepatitis patients and to assess the clinical and laboratory findings prospectively. Methods: Thirty-six patitents with negative for markers of viral hepatitis B and viral hepatitis C and who gave no history of alcohol consumption or consumption less than 20 grams of ethanol per day were recruited with consented for liver biopsy and blood tests for identify the etiology of chronic hepatitis. Results: Eight of 36 patients (22.2%) were classified as cryptogenic chronic hepatitis. Most patients (72.2%) exhibited fatty metamorphosis of the liver which included steatosis as well as steatohepatitis. There were statistically significant differences between the fatty metamorphosis group and the cryptogenic chronic hepatitis group with regarding to fasting blood sugar, serum alkaline phosphatase, serum ferritin and histologically necroinflammatory grading score (p<0.05). Between the steatosis and the steatohepatitis, body mass index (BMI) was the only factor showing statistically significant difference (p = 0.02). Conclusion: Steatohepatitis and steatosis are the most common findings of non alcoholic and non viral hepatitis B, non viral hepatitis C chronic hepatitis, especially in the diabetic, the obese patients and those with high serum ferritin level. Cryptogenic chronic hepatitis is not uncommon in our study in Thai patients